Social Memory and the Role of the Hippocampal CA2 Region - Tzakis, Nikolaos; Holahan, Matthew R. (Frontiers in Behavioral Neuroscience, 2019)
The CA2 region of the hippocampus is a somewhat obscure area lacking in an understanding of its form and function. Until recently, the CA2 has been thought of as merely an extension of the CA3, with some referring to it as the CA3a region. Recent investigations into this area have not only delineated the CA2, but also defined it as a region distinct from both CA1 and CA3, with a unique set of cortical inputs and outputs, and contributions to cognitive processes. One such process that has been shown to depend on the CA2 is the ability to recognize a novel conspecific, known as social recognition memory. Here, we review these findings and discuss the parallels between CA2 dysfunction and social impairments.